New Aspects in Thrombosis Research: Possible Role of Mast Cells as Profibrinolytic and Antithrombotic Cells - Valent, P.; Baghestanian, M.; Bankl, H. C.; Sillaber, C.; Sperr, W. R.; Wojta, J.; Binder, B. R.; Lechner, K. (Thrombosis and Haemostasis, 2002)
Venous thromboembolism represents a significant cause of morbidity worldwide. The factors that underly thrombophilia are manifold. The concept of Virchow defines the well known triad of stasis, humoral factors, and pathologies of the vascular wall. In the current article, an additional factor, the “accumulation of repair cells” is discussed. This novel concept highlights the mast cell that accumulates around thrombosed vessels and provides a number of important repair molecules including heparin, profibrinolytic tPA, and fibrinogenolytic β-tryptase. Thus, mast cell recruitment and activation may result in local thrombolysis and prevention of coagulation. In line with this concept, mast cell-deficient mice are more susceptible to lethal thrombogenic stimuli compared to normal mice. The factors (cytokines) that trigger mast cell accumulation and release of repair molecules have also been identified – the most important one appears to be stem cell factor (SCF). All in all, our novel concept suggests that the patho-physiology of thrombosis may involve a “physiologic” cell that provides the same repair molecules that are used for treatment of thrombotic disorders by the physician. Whether an altered availability of components of this cellular repair system can predispose for thrombophilia remains to be determined.
Keywords: Thrombophilia; repair; mast cells; heparin; tPA; fibrinolysis